Do plunderphonics ao noise: Narrativas do ruído e da colagem a partir do binômio forma e conteúdo - Paulino, Rafael Diniz (2017)
This research has as main objective to create a dialogue between the study on some practices that incorporate the noise and musical collage, in its poetics, and our work of creation. Among such practices, we highlight noise, plunderphonics and radio-art. Our way of thinking about those themes consisted to relate them to certain concepts and theoretical assumptions. Some of these were drawn from the concept of the epic theater proposed by the German playwright and poet Bertold Brecht, especially his notions of narrative forms and how he understands form and content. We use the jargon of “morphology of the open work” proposed by Valério Fiel da Costa, and from this we use some basic terms, such as: invariance, morphological nexus and morphological limit. Based on these supports, we reflect on what identifies the practices under analysis regarding its sociocultural, historical, technical and expressive issues. Concerning our work of creation, three compositions are addressed: s_Septem (2015), Segunda-feira... sol de inverno (2015) and Direito de feedback (2016). The first, s_Septem, is an acousmatic piece, the result of a studio performance; the others, Segunda-feira...sol de inverno and Direito de feedback are audiovisual pieces, and were composed from performances and studio montages.